A Streamlined Mutation Detection System: Multicolor Post-PCR Fluorescence Labeling and Single-Strand Conformational Polymorphism Analysis by Capillary Electrophoresis - Inazuka, Masakazu; Wenz, Hans-Michael; Sakabe, Munechika; Tahira, Tomoko; Hayashi, Kenshi (Genome Research, 1997)
Effective use of knowledge of human genome sequences in studies of hereditary diseases or cancer heavily depends on efficient methods for detection of mutations in individual samples. We describe here a simple and efficient mutation scanning system in which PCR products arepost-labeled with two different fluorescent dyes in one tube, and analyzed by an automatedcapillary electrophoresis system using single-strand conformation polymorphism (SSCP) conditions (PLACE–SSCP). With the appropriate use of an internal control DNA, differences in electrophoretic mobilities between a reference and samples are precisely evaluated, then the presence of mutations is statistically judged. Thirty-three of 34 known mutations in fragments of three unrelated sequence contexts up to 741 bp were detected using one electrophoresis condition at the confidence level of <0.3% false positive. All the mutations were detected by analyzing at two temperatures. The described system has the advantage of little human intervention, short analysis time, high sensitivity, and objectivity of data interpretation.